Evolving views and practices of antiretroviral treatment prescribers in Australia. Issue 5 (16th March 2015) - Mao, Limin; Adam, Philippe C G; Kippax, Susan; Crooks, Levinia; Post, Jeffrey J; Kidd, Michael R; Slavin, Sean; Wright, Edwina J; de Wit, John B F
Abstract: Objective: To examine whether there have been recent changes in Australian antiretroviral treatment (ART) prescribers' perceptions and practices relating to early ART initiation, which was defined as commencing ART when a patient's CD4+ T‐cell count approaches 500 cells/mm 3 or immediately after a patient is diagnosed with HIV. Design, participants and setting : Self‐completed, anonymous, cross‐sectional surveys, targeting all ART prescribers in Australia, were conducted online in 2012 and 2013. The surveys included questions on prescriber factors, CD4+ T‐cell count at which prescribers would most strongly recommend ART initiation, and perceived patient characteristics that could change prescribers' practices of early initiation of ART. Main outcome measure s : Proportions of ART prescribers recommending early ART initiation. Results: We analysed responses from 108 participants in 2012 and 82 participants in 2013. In both years, more male than female prescribers participated. The median age of participants was 49 years in 2012 and 50 years in 2013. In both rounds, over 60% had more than 10 years' experience in treating HIV‐positive patients. More prescribers in 2013 stated that they would most strongly recommend early ART initiation compared with those in 2012 (50.0% [95% CI, 38.7%–61.3%] v 26.9% [95% CI, 18.8%–36.2%]; P  = 0.001). The prescribers' primary concern was more about individual patient than public health benefit. Out of 824 patients for whom ART was initiated, as reported by prescribers in 2013, only 108 (13.1% [95% CI, 10.9%–15.6%]) were given ART primarily to prevent onward HIV transmission. The number of patients for whom ART was initiated was significantly associated with prescribers' HIV caseload even after adjusting for prescriber type (adjusted odds ratio, 1.73 [95% CI, 1.47–2.03]; P  < 0.001); of the 37 who had initiated ART for 10 or more patients, 29 had a high HIV caseload. In 2013, 60 prescribers (73.2% [95% CI, 62.2%–82.4%]) reported that they routinely recommended ART to treatment‐naive, asymptomatic patients with a CD4+ T‐cell count of 350–500 cells/mm 3 . Conclusion: Our findings show increasing acceptance of and support for early ART initiation primarily as treatment and not as prevention.